2018
DOI: 10.3126/nccj.v3i1.20258
|View full text |Cite
|
Sign up to set email alerts
|

Management Accounting and Control System

Abstract: A larger entity of the cost management system which assists executives in fulfilling organizational objectives is known as management accounting and control system (MACS). It is used for planning, monitoring and control of different organizational activities, to optimize the use of resources, to support the process of decision making and to the performance evaluation process. The scope of the MACS can be divided into two broad groups: technical considerations and behavioral considerations. Technical considerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
2
9
0
Order By: Relevance
“…This result is in accordance with previous research (Dahal, 2018;Dasrita et al, 2015;Lau & Oger, 2019). The performance measurement system provides positive motivation for employees always to improve the quality of their performance and as a basis for the follow-up to increase employee competency.…”
Section: Effect Of Performance Measurement Systems On Tamsupporting
confidence: 94%
See 2 more Smart Citations
“…This result is in accordance with previous research (Dahal, 2018;Dasrita et al, 2015;Lau & Oger, 2019). The performance measurement system provides positive motivation for employees always to improve the quality of their performance and as a basis for the follow-up to increase employee competency.…”
Section: Effect Of Performance Measurement Systems On Tamsupporting
confidence: 94%
“…Not including nonfinancial factors as elements in performance measurement causes improvements and innovations that are carried out unsustainably. The modern approach emphasizes the balance between financial and non-financial factors (Dahal, 2018). Previous studies have shown that a good performance measurement system affects employee performance (Dahal, 2018;Dasrita et al, 2015;Lau & Oger, 2019).…”
Section: Performance Measurement Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, management accounting systems provide managers with critical financial and nonfinancial information for planning, controlling and decision-making (Ahrens and Chapman, 2007). These systems also collect, classify, summarize and report information for performance measurement, continuous improvement processes and resource optimization (Drury, 2018; Dahal, 2018). Hence, MAS are accounting instruments that assess resource demands and whether resources are allocated efficiently and effectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, accounting systems are not only responsible for facilitating economically sustainable decisions but also serve as a rationalization instrument for decisions that have already been made (Dahal, 2018). Specifically, management accounting systems provide managers with critical financial and nonfinancial information for planning, controlling and decision-making (Ahrens and Chapman, 2007).…”
Section: Literature Review 21 Management Accounting Systems (Mas) And...mentioning
confidence: 99%